Analisis Kebutuhan Pembelajaran Bahasa Inggris pada Mahasiswa Kelas Karyawan - Rita Karmila Sari (Universitas Indraprasta PGRI Jakarta, 2019)
The purpose of this study was to analyze the needs of employee class for learning English to be used as a reference for curriculum development and making syllabus for English for Specific Purposes (ESP). This study identified students’ motivations, constraints faced by the students and the needs for learning English based on four basic language skills. This research uses descriptive analysis method with quantitative approach. Data was obtained through distributing questionnaires to 159 respondents from first semester students of the 2018/2019 academic year at one of the private university in the East Jakarta. They are generally aged 21-29 years with the last education of vocational schools and have jobs as private employees. The identification of their language skill shows that generally the respondents have English basic skill. Analysis of questionnaire data states that students' motivation in learning English is to improve academic grades and be able to speak English. While their main constraints are limited vocabulary and not understanding English grammar. The results of needs analysis concluded that students need English to understand texts and instructions along with to obtain information that is useful for their studies.